The Long-Term Life-Cycle of Nevado de Toluca Volcano (Mexico): Insights Into the Origin of Petrologic Modes - Weber, Gregor; Caricchi, Luca; Arce, José Luis (Frontiers in Earth Science, 2020)
The petrologic diversity of volcanic rocks reflects the dynamics of magma reservoirs and the temporal evolution of magma chemistry can provide valuable information for hazard assessment. While some stratovolcanoes monotonously produce intermediate magmas (55-68 wt.% SiO2), dominantly erupted magma types (e.g. basaltic andesite, andesite or dacite) frequently differ even between neighboring volcanoes. If such differences arise due to thermal maturation processes over time or are predetermined by other properties of magmatic systems remains poorly understood. This study helps to elucidate the underlying factors modulating the chemistry of the magma preferentially erupted by Nevado de Toluca volcano in Central Mexico. We present a new dataset of bulk-rock and mineral chemistry spanning the entire 1.5 Million years of the volcanos’ eruptive history. The results reveal that Nevado de Toluca dacites and minor andesite originate in a stable configuration of pre-eruptive processes and plumbing system architecture by hybridization between an upper crustal silicic mush and deeper sourced basaltic andesite magmas. Yet, a subtle trend towards increasing silica content with time (2 wt.% in 1.5 Ma) and episodicity in magma hybridization conditions are observed. We use thermal simulations of pulsed magma injection to probe the controlling variables on the temporal variation and compositional mode of magma geochemistry. The results show that the subtle temporal trend towards increasing bulk-rock SiO2 content is plausibly explained by slightly dropping recharge rates and continued upper crustal reservoir growth. Our modelling also shows that the dominant composition of eruptible magmas (“petrologic mode”) can shift as a function of magma flux, extrusive:intrusive ratio and temperature of the recharge magma. A comparison of SiO2 whole rock distributions for monotonous Mexican stratovolcanoes and their peripheral cones shows that their petrologic modes vary in concert, indicating that the recharge magma chemistry or temperature is a major control on the preferentially erupted magma composition for these volcanoes.